Direct Incorporation of [11C]CO2 into Asymmetric [11C]Carbonates. (10th December 2018) - Haji Dheere, Abdul Karim; Bongarzone, Salvatore; Shakir, Dinah; Gee, Antony
Abstract : A novel carbon-11 radiolabelling methodology for the synthesis of the dialkylcarbonate functional group has been developed. The method uses cyclotron-produced short-lived [ 11 C]CO2 (half-life 20.4 min) directly from the cyclotron target in a one-pot synthesis. Alcohol in the presence of base trapped [ 11 C]CO2 efficiently forming an [ 11 C]alkylcarbonate intermediate that subsequently reacted with an alkylchloride producing the di-substituted [ 11 C]carbonate (34% radiochemical yield, determined by radio-HPLC) in 5 minutes from the end of [ 11 C]CO2 cyclotron delivery.